2019
DOI: 10.1155/2019/3696825
|View full text |Cite
|
Sign up to set email alerts
|

Increased Heart Rate Variability following Elective Percutaneous Coronary Intervention in Patients with Stable Coronary Artery Disease and Preprocedural Anxiety

Abstract: Background. There is a strong association between chronic ischemia and autonomic imbalance. Percutaneous coronary intervention (PCI) may restore autonomic balance in patients with stable coronary artery disease (SCAD), which is characterized by increased heart rate variability (HRV). Anxiety is often found in patients who are going to undergo invasive procedures and has been identified to induce autonomic imbalance. The aim of our study is to identify the impact of preprocedural anxiety on increased HRV follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The increase of SDNN post-PCI was significantly higher in subjects without pre-procedural anxiety compared with those with anxiety. [6] In the present study, during pre-PCI ECG recordings, angina/dyspnoea/anxiety persisted in a few patients. In another study by Delewi et al, [17] anxiety levels were measured using the self-reported visual analogue scale and observed that the pre-procedural anxiety scores obtained were the highest.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…The increase of SDNN post-PCI was significantly higher in subjects without pre-procedural anxiety compared with those with anxiety. [6] In the present study, during pre-PCI ECG recordings, angina/dyspnoea/anxiety persisted in a few patients. In another study by Delewi et al, [17] anxiety levels were measured using the self-reported visual analogue scale and observed that the pre-procedural anxiety scores obtained were the highest.…”
Section: Discussionsupporting
confidence: 45%
“…Coronary artery disease patients tend to have increased sympathetic activity as ischemic event induces this enhanced sympathetic function. [5][6][7][8] Elimination of myocardial ischemia could bring back the autonomic balance state to normal. [6][7][8][9] Only a few studies looked at the role of HRV analyses in the restoration of cardiac autonomic balance in patients with ischaemic heart disease (IHD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation